NEW HIGH-EFFICIENT EQUIPMENT FOR ELECTROMAGNETIC MIXING OF LIQUID METAL AT CONTINU¬OUS CASTING OF ROUND BILLETS OF SPECIAL ALLOYS AND ALLOYED GRADES OF STEEL - S. I. Shahov; A. S. Smoljakov; V. G. Grachev; A. A. Solovjov (Литьë и металлургия)
It is shown that devices of electromagnetic mixing in crystallizer produced by AHK «VNIIMETMASH» – ZAO «ETM» in comparison with foreign analogs enable to save current consumption to 6 million kilowatt/hour annually.